Crack Growth Behavior through Wall Pipes under Impact Load and Hygrothremal Environment - Khaled, Ali Jamal; Hussain, Ahmed Abdul (Al-Khwarizmi Engineering Journal, 2018)
This research concerns study the crack growth in the wall of pipes made of low carbon steel under the impact load and using the effect of hygrothermal (rate of moisture 50% and 50℃ temperature). The environmental conditions were controlled using high accuracy digital control with sensors. The pipe have a crack already. The test was performed and on two type of specimens, one have length of 100cm and other have length 50cm. The results were, when the humidity was applied to the pipe, the crack would enhance to growth (i.e. the number of cycles needed to growth the crack will reduce). In addition, when the temperature was increase the number of cycles needed to growth the crack are reduced because the effect of heat on the mechanical properties of the material. In addition, when the test performed on the specimens of length 50cm the number of cycles needed to growth the crack is increase because the effect of bending stress on the pipes.